Collagen supplementation augments changes in patellar tendon properties in female soccer players - Lee, Joonsung; Bridge, Josh E.; Clark, David R.; Stewart, Claire E.; Erskine, Robert M. (Frontiers in Physiology, 2023)
We investigated the effect of collagen hydrolysate supplementation on changes in patellar tendon (PT) properties after 10 weeks’ training in female soccer players from a Football Association Women’s Super League Under 21s squad. We pair-matched n=17 players (age: 17±0.9 years; height: 1.66±0.06m; mass: 58.8±8.1kg) for baseline knee extensor (KE) maximum isometric voluntary contraction (MIVC) torque, age, height, and body mass, and randomly assigned them to collagen (COL) or placebo (PLA) groups (COL n=8, PLA n=9). Participants consumed 30g collagen hydrolysate supplementation or energy-matched PLA (36.5g maltodextrin, 8.4g fructose) and plus both groups consumed 500mg vitamin C, after each training session, which comprised bodyweight strength-, plyometric- and/or pitch-based exercise 3 days/week for 10 weeks in-season. We assessed KE MIVC torque, vastus lateralis muscle thickness and PT properties using isokinetic dynamometry and ultrasonography before and after 10 weeks’ soccer training. KE MIVC torque, muscle thickness and tendon cross-sectional area did not change after training in either group. However, COL increased PT stiffness (COL, +18.0±12.2 % [d=1.11] vs. PLA, +5.1±10.4 % [d=0.23], P=0.049) and Young’s modulus (COL, +17.3±11.9 % [d=1.21] vs. PLA, +4.8±10.3 % [d=0.23], P=0.035) more than PLA. Thus, 10 weeks’ in-season soccer training with COL increased PT mechanical and material properties more than soccer training alone in high-level female soccer players. Future studies should investigate if collagen hydrolysate supplementation can improve specific aspects of female soccer performance requiring rapid transference of force, and if it can help mitigate injury risk in this under-researched population.